2006
DOI: 10.1897/05-615r.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cyanobacterial toxins and cyanobacterial cell‐free crude extract on germination of alfalfa (Medicago sativa) and induction of oxidative stress

Abstract: Cyanobacterial toxins have adverse effects on both terrestrial and aquatic plants. Microcystins are cyclic heptapeptides and an important group of cyanotoxins. When lake water contaminated with cyanobacterial blooms is used for spray irrigation, these toxins can come in contact with agricultural plants. During the exposure to these toxins, reactive oxygen species can form. These reactive oxygen species have a strong reactivity and are able to interact with other cellular compounds (lipids, protein, and DNA). P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
95
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(110 citation statements)
references
References 27 publications
13
95
0
1
Order By: Relevance
“…2a), especially at high exposure concentrations (MCLR ≥3 g/ml, or LAS ≥20 g/ml or their mixture ≥3 + 10 g/ml), indicating that individual and joint exposure to the two toxicants in L. minor triggered antioxidant reactions. Increased SOD activity with MCLR treatment was consistent with other results [11,[48][49][50], but little research has focused on SOD activity after LAS exposure [24]. SOD activity was more strongly reduced after 8 d exposure compared with 2 d (Fig.…”
Section: Mclr ( G/ml)supporting
confidence: 89%
“…2a), especially at high exposure concentrations (MCLR ≥3 g/ml, or LAS ≥20 g/ml or their mixture ≥3 + 10 g/ml), indicating that individual and joint exposure to the two toxicants in L. minor triggered antioxidant reactions. Increased SOD activity with MCLR treatment was consistent with other results [11,[48][49][50], but little research has focused on SOD activity after LAS exposure [24]. SOD activity was more strongly reduced after 8 d exposure compared with 2 d (Fig.…”
Section: Mclr ( G/ml)supporting
confidence: 89%
“…This increased SOD activity with MCLR treatment was consistent with results of Chen et al (2004), who demonstrated that lower concentrations of MCs (0.024-0.12 lg ml -1 ) significantly increased SOD activity in rice (Oryza sativa L.) seedlings, whereas higher concentrations (0.6-3 lg ml -1 ) only slightly increased SOD activity. Exposure to 5 lg l -1 MCLR for 2 h for the aquatic macrophyte Ceratophyllum demersum, or 7 days for alfalfa (Medicago sativa), significantly increased SOD activity (Pflugmacher 2004;Pflugmacher et al 2006). Furthermore, exposure to MCLR concentrations as low as 0.5 lg l -1 increased SOD activity in spinach (Spinacia oleracea) variants (Pflugmacher et al 2007).…”
Section: Toxic Effect Of Mclr Las and Their Combination On Germinatimentioning
confidence: 99%
“…Up to 8.4-25.0 lg ml -1 of total MCs has been reported in several bloom samples (Máthé et al 2007). In many countries, the cyanotoxin-containing water is used as an irrigation source (Chen et al 2004;Pflugmacher et al 2006Pflugmacher et al , 2007, and/or some cyanobacteria are directly discharged as organic fertilizers to farms (Chen et al 2006). Therefore, it is possible for a large amount of MCs to be released into cropland and crops may be at potential risk of exposure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the effects of MCYSTs on animals and humans, water contaminated with MCYSTs that is used for irrigation may inhibit germination and plant growth causing crop failures (Pflugmacher et al 2006). The exposure of edible crop plants to MCYSTs is also a concern for human health, as the toxins can accumulate in plant tissues (McElhiney et al 2001, Jarvenpaa et al 2007) and be transmitted to humans through the food chain.…”
Section: Introductionmentioning
confidence: 99%